PENERAPAN MODUL PEMBELAJARAN BERBASIS INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR MAHASISWA - Cut Nurmaliah; M. Ali Sarong; Yusra Yusra (Postgraduate, University of Mataram, 2021)
The purpose of this study was to determine the application of inquiry-based learning modules to science process skills and student learning outcomes in aquatic ecology courses at the Faculty of Fisheries and Marine Sciences, Teuku Umar University. This research method is pre-experimental with one group pretest-posttest design. The population in this study were all students at the Faculty of Fisheries and Marine Sciences, Teuku Umar University. The sample in this study was students in the odd semester of the 2019/2020 Academic Year in the Fisheries and Marine Studies Program, totaling 105 students and 5 classes taking Aquatic Ecology courses, namely the Fisheries, Aquaculture and Aquatic Resources study program. The results showed that the application of inquiry-based learning modules could improve science process skills in aquatic ecology courses at the Faculty of Fisheries and Marine Sciences, Teuku Umar University. The results of the analysis prove that the average percentage of students' Science Process Skills on indicators of observation is 85.08, interpretation is 60.32, classification is 92.06, communication is 77.78, experiment is 70.16, and principle is 66.98. The application of inquiry-based learning modules can improve student learning outcomes in aquatic ecology courses at the Faculty of Fisheries and Marine Sciences, Teuku Umar University. The results of the average increase in student learning outcomes pretest 42.93, posttest 76.5, and N-gain 62.82. While the results of the average difference test indicate that the significance value is 0.013 <0.05, meaning that there is a difference in the average student learning outcomes before and after applying the guided inquiry module. Based on the results of research that has been done, it can be concluded that there is an increase in science process skills and student learning outcomes